Perceptions of Prices and Reference Groups in West Kalimantan Students on the Decision to Use Airplanes - M. Rizky Ramadan; Walid Jumlad (CV. Rayyan Dwi Bharata, 2023)
In this era of progress, there are many phenomena that occur, which indicate a shift in behavior models in society where initially airplanes were only used by certain groups of people, but with the development of the times and the increasingly advanced world of technological developments, now airplanes can be enjoyed by all lines of society. Current conditions make marketers try to keep abreast of the development trend of increasingly changing consumer behavior. The purpose of this study was to look at the influence of reference group variables and price perceptions in West Kalimantan students on the decision to use airplanes. The approach used by researchers in this paper is a quantitative approach. where researchers conducted a study in the form of distributing questionnaires or questionnaires which were then filled in by respondents, namely students from the Province of West Kalimantan totaling 100 respondents. Then the data will be processed using data analysis in the form of a classical assumption test and several analytical techniques such as multiple linear regression equations, T-test, F-test to the Coefficient of Determination. The results of data processing show that price perceptions and reference groups in West Kalimantan students simultaneously have a significant influence on increasing the decision to use aircraft. Perceived prices and reference groups of West Kalimantan students partially have a significant influence on increasing the decision to use aircraft. With the results of testing the coefficient of determination, it shows that the variable influence of service quality and availability of facilities on passenger satisfaction is 0.448 (44.8%).